Concepts of biology - Mader, Sylvia S. (McGraw-Hill, 2009)
The laboratories are coordinated with Concepts of Biology, a general biology text that covers all fields of biology. This manual may also be used in coordination with other texts and can be adapted to a variety of course orientations and designs. Thirteen laboratories have been singled out in the Table of Contents as especially appropriate for a single semester course. Then, too, many activitie may be performed as demonstrations, thereby shortening the time required to cover a particular concept